Investigation of a family of dual‐output coupled/decoupled switched capacitor converter for low‐power applications. Issue 3 (4th April 2019) - Subburaj, Vivekanandan; Zhaikhan, Ainur; Jena, Debashisha; Perumal, Parthiban; Mustafa, Yerzhan; Ruderman, Alex
Abstract : Here, accurate transresistance calculations for the coupled case and mathematical modelling are provided for dual input–output switched capacitor converter (SCC). This converter offers two different output voltages and produces 36 voltage conversion ratios. The dual input–output SCC is portable and operates by considering either sources or the combination of both V s 1 and V s 2 as input sources. The proposed dual input–output SCC has the ability to vary 54 voltage ratios. An efficient low‐power SCC is designed for an input voltage range of 1.5–5 V and it gives dual‐output voltages of 1–10 V. The proposed converter can operate in both buck and boost modes. The SCC has high drive capability of load current in the range of 10 µA to 100 mA that is adjusted by varying the operating frequency. The accurate equivalent resistance for both coupled and decoupled load cases is found and validated. The results are verified through PSIM simulations and validated experimentally. The mathematical, simulation, and experimental results give excellent proof for proposing the newly designed converter for applications requiring large conversion ratios eliminating inductors.